Persuasive Communication of Village Apparatus in Disciplining Residents Implementing Covid-19 Health Protocols - Nanda Rizkiyah; Didik Hariyanto (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to determine the role of persuasive communication of the Kali Pecabean Village apparatus in disciplining residents to implement health protocols during the Coid-19 pandemic. This research uses a qualitative descriptive method. The object of this research is persuasive communication regarding health protocols carried out by village officials. The data collection process is carried out by means of observation, in-depth interviews and documentation, then the data will be analyzed in three ways, namely data reduction, data presentation and finally drawing conclusions. The results show that (1) Persuasive communication of village officials in disciplining residents in implementing health protocols is considered very effective by the community because it has quite good changes. From changes in society that finally wear masks and avoid crowds. (2) The strengthening of the arguments of the Kali Pecabean community does not only come from communications made by the Village apparatus, but from public knowledge related to the increasing Covid-19 cases and providing evidence that Covid-19 exists. (3) The psychological attractiveness of the Kali Pecabean village community is influenced by the large number of people exposed to Covid-19 in the Pecabean River area, making it one of the factors for community change regarding the importance of maintaining health and implementing health protocol discipline.